2015
DOI: 10.1007/s00404-015-3861-4
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and its relation with ionic calcium, parathyroid hormone, maternal and neonatal characteristics in pregnancy after roux-en-Y gastric bypass

Abstract: The post-RYGB pregnant women showed an elevated serum inadequacy (deficiency or insufficiency) of 25(OH)D during pregnancy. Maternal vitamin D status showed no association with maternal variables, except UTI, and the neonatal variables analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Several studies have examined the relationship between post-BS pregnancy, calcium and vitamin D metabolism and found a Vitamin D deficiency in 3% to over 70% of pregnant women, depending on the BS procedure [51, 54, 70]. There is a physiological increase in the need of vitamin D and calcitriol during pregnancy seemingly related to the calcium transfer to the fetus, particularly in the last trimester [70].…”
Section: Challenges and Benefits Of Bariatric Surgery Before Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined the relationship between post-BS pregnancy, calcium and vitamin D metabolism and found a Vitamin D deficiency in 3% to over 70% of pregnant women, depending on the BS procedure [51, 54, 70]. There is a physiological increase in the need of vitamin D and calcitriol during pregnancy seemingly related to the calcium transfer to the fetus, particularly in the last trimester [70].…”
Section: Challenges and Benefits Of Bariatric Surgery Before Pregnancymentioning
confidence: 99%
“…The prevalence of elevated PTH levels (> 65 pg/ml) was highest in the third trimester with 32.6% of subjects. However, no adverse pregnancy outcomes were detected [70]. A large retrospective study conducted in Taiwan pointed out that there is a high incidence of post-surgery secondary hyperparathyroidism for all procedures (37.2%) which could lead to a higher long-term fracture risk, however, the available data ins still controversial.…”
Section: Challenges and Benefits Of Bariatric Surgery Before Pregnancymentioning
confidence: 99%
“…Another study found significantly higher level folate serum levels after surgery and during pregnancy due to supplementation ( Mead et al , 2014 ). Medeiros et al (2016) found that 72% of women after RYGB had an inadequate vitamin D status during the first trimester despite daily vitamin D supplementation.…”
Section: Resultsmentioning
confidence: 99%
“…Higher calcium doses in pregnancies after bariatric surgery are recommended compared with normal pregnancies. Calcium deficiency was reported in 15.2% in the first and second trimesters and 20% in the third trimester in pregnant women after RYGB [ 72 ]. PTH excursions were found in 19.6, 30.4, and 32.6% from first to third trimester, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In postbariatric populations, doses up to 6000 IU/d are discussed for nonpregnant women [ 6 ]. A study evaluating vitamin D status and its relations with ionic calcium and parathyroid hormone (PTH) in pregnant women after RYGB found vitamin D deficiency (≤20 ng/mL) or insufficiency (>20–30 ng/mL) above 70% in all trimesters [ 72 ]. Negative correlations between calcium and PTH as well as an association of vitamin D with higher risk of urinary tract infection were reported.…”
Section: Resultsmentioning
confidence: 99%